A new method of virtual direct torque control of doubly fed induction generator for grid connection - Mahmoud Zadehbagheri; Tole Sutikno; Mohammad Javad Kiani (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Over the past few years, due to the shortage of fossil fuels and their unwanted environmental impacts, the use of renewable energy has vastly increased. Among them is wind power, which has been at the center of attention as one of the most important renewable energies. Many studies have been conducted regarding wind farms with variable speeds. Among these, the doubly fed induction generator (DFIG) has been of utmost importance due to its capability of separately controlling the active and reactive power, reducing the nominal converter capacity, maintaining constant variable speed frequency, and improving quality. The goal of this study is to control the synchronizing and network connection to the DFIG such that when connected to the network, no pulse is seen in the torque, rotor current, or stator. The method used in this study is known as virtual torque, which is derived from direct torque control, but instead of an electromagnetic torque, we use a virtual one. To implement this method, it is only required to measure the network voltage, current, and rotor position, and changing the control algorithm from synchronizing to grid connection only includes some changes in the flux references and torque, and calculating the electromagnetic torque instead of the virtual one.